2018
DOI: 10.1007/s11244-018-0989-z
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Oxide-TiO2 Nanocomposite Type Photocatalyst for Methanol Photocatalytic Reforming Reaction

Abstract: Graphite-oxide/TiO 2 (GO/TiO 2 ) composite materials were prepared by heterocoagulation method from Brodie's graphiteoxide (GO) in order to test them as catalysts in the methanol photocatalytic reforming reaction in liquid phase. The preparation of the composite itself resulted in only little changes in the structure of GO as it was indicated by attenuated total reflection infrared (ATR-IR) and 13 C magic-angle spinning nuclear magnetic resonance ( 13 C MAS NMR) spectroscopic measurements. However, during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Graphene oxide (GO) has been widely applied to improve the photocatalytic activity [50][51][52][53]. Majrik et al prepared GO modified TiO 2 by a hetero-coagulation method and evaluated its photocatalytic activity of methanol reforming [54]. It was found that with 2% of GO in the composite (GO-TiO 2 ), the photocatalytic production rate of H 2 was more than 5 times higher than pure TiO 2 .…”
Section: Photocatalytic Reforming Of Ethanolmentioning
confidence: 99%
“…Graphene oxide (GO) has been widely applied to improve the photocatalytic activity [50][51][52][53]. Majrik et al prepared GO modified TiO 2 by a hetero-coagulation method and evaluated its photocatalytic activity of methanol reforming [54]. It was found that with 2% of GO in the composite (GO-TiO 2 ), the photocatalytic production rate of H 2 was more than 5 times higher than pure TiO 2 .…”
Section: Photocatalytic Reforming Of Ethanolmentioning
confidence: 99%
“…These included doping with various non-metals [2,6,10,14], modifying with noble metals [15,16,17], sensitizing with dyes [18,19], synthesizing TiO 2 with various morphologies [11,20], and coupling TiO 2 with other semiconductors [21,22,23]. A promising direction is the use of different forms of carbon, e.g., carbon nanotubes [2,24,25,26], graphite oxide [27], activated carbon [7], graphene [28], and graphene oxide [1]. Carbon materials have the potential of improving the photocatalytic activity of TiO 2 by (1) narrowing the band gap of the semiconductor, (2) decreasing the recombination rate of photogenerated charge carriers, (3) providing more active reaction/adsorption centers in greater amounts and higher surface area, (4) acting as a photosensitizer for the photocatalytic reactions, and (5) prolonging the lifespan of charge carriers [27,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A promising direction is the use of different forms of carbon, e.g., carbon nanotubes [2,24,25,26], graphite oxide [27], activated carbon [7], graphene [28], and graphene oxide [1]. Carbon materials have the potential of improving the photocatalytic activity of TiO 2 by (1) narrowing the band gap of the semiconductor, (2) decreasing the recombination rate of photogenerated charge carriers, (3) providing more active reaction/adsorption centers in greater amounts and higher surface area, (4) acting as a photosensitizer for the photocatalytic reactions, and (5) prolonging the lifespan of charge carriers [27,29,30]. There are numerous examples described in the literature where most of these advantageous effects were observed when amorphous (that is, not crystalline) carbon was used [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In the topic of composites it is worth highlighting that a promising direction is to make composites using different forms of carbon, e.g. carbon nanotubes [94,[176][177][178], graphite oxide [179], activated carbon [180], graphene [181] and graphene oxide [95].…”
Section: Construction Of Compositesmentioning
confidence: 99%
“…Following the oxygen rich modification of anatase, rutile and even amorphous phase was investigated based on the following points. Carbon materials have the potential of improving the photocatalytic activity of TiO2 by (i) narrowing the band gap of the semiconductor; (ii) decreasing the recombination rate of photogenerated charge carriers; (iii) providing more active reaction/adsorption centers in greater amounts and higher surface area; (iv) acting as a photosensitizer for the photocatalytic reactions; (v) prolonging the lifespan of charge carriers [36,179,219]. There are numerous examples described in the literature where most of these advantageous effects were observed even when amorphous (i.e.…”
Section: Morphological Modification [73 99]mentioning
confidence: 99%